Hypnosis Antenatal Training for Childbirth: a randomised controlled trial. Issue 10 (3rd July 2013) - Cyna, AM; Crowther, CA; Robinson, JS; Andrew, MI; Antoniou, G; Baghurst, P
Abstract : Objective: To determine the use of pharmacologic analgesia during childbirth when antenatal hypnosis is added to standard care. Design: Randomised controlled clinical trial, conducted from December 2005 to December 2010. Setting: The largest tertiary referral centre for maternity care in South Australia. Population: A cohort of 448 women at >34 weeks of gestation, with a singleton pregnancy and cephalic presentation, planning a vaginal birth. Exclusions were: the need for an interpreter; pre‐existing pain; psychiatric illness; younger than 18 years; and previous experience of hypnosis for childbirth. Methods: All participants received usual care. The group of women termed Hypnosis + CD (hypnotherapist guided) were offered three antenatal live hypnosis sessions plus each session's corresponding audio CD for further practise, as well as a final fourth CD to listen to during labour. The group of women termed CD only (nurse administered) were played the same antenatal hypnosis CDs as group 1, but did not receive live hypnosis training. The control group participants were given no additional intervention or CDs. Main outcome measure: Use of pharmacological analgesia during labour and childbirth. Results: No difference in the use of pharmacological analgesia during labour and childbirth was found comparing hypnosis + CD with control (81.2 versus 76.2%; relative risk, RR 1.07; 95% confidence interval, 95% CI 0.95–1.20), or comparing CD only with control (76.9 versus 76.2%, RR 1.01, 95% CI 0.89–1.15). Conclusions: Antenatal group hypnosis using the Hypnosis Antenatal Training for Childbirth (HATCh) intervention in late pregnancy does not reduce the use of pharmacological analgesia during labour and childbirth.